Vitamin D Deficiency Rickets and COVID-19 Pandemic - Guwani Liyanage; Yashica de Silva (Hindawi Limited, 2021)
In a breastfed infant, the main source of vitamin D comes from the mother. Thus, maternal vitamin D deficiency is the key reason for vitamin D deficiency (VDD) and rickets during infancy. As they grow older, inadequate sun exposure, diet and lack of supplements also contribute. Individuals with darker skin require at least three to five times longer exposure to the sun than a person with lighter skin to produce adequate endogenous vitamin D. Not many food items naturally contain vitamin D; most of those are less affordable to the poor. We report an 18-month-old child with vitamin D deficiency rickets during strict self-isolation measures during the coronavirus disease 2019 (COVID-19) pandemic. Prolonged periods of confining indoors, low dietary intake of vitamin D, economic distress, maternal deficiency, and nonsupplementation could have contributed to vitamin D deficiency rickets in this child. During an unprecedented pandemic of this nature, simple sun exposure and diet advice may suffice for most. This case report highlights the importance of strengthening individuals and communities with information and formulating strong public health policies to prevent vitamin D deficiency.